Photosynthetic adaptability in mature and young leaves of Medicago sativa L. seedlings under transplanted condition from greenhouse to sunlight - Li, Mengsha; Sui, Xin; Zhang, Huihui; Xu, Nan; Zhang, Tong; Zhou, Liping; Wang, Hua; Mu, Liqiang; Zhang, Yue (Bangladesh Journal of Botany, 2019)
The effect of transplanting alfalfa (Medicago sativa) seedlings from artificial, low-intensity light into bright sunlight was investigated. The variance of photosynthetic function in young and mature leaves was investigated in plants grown in a low-light greenhouse environment (controls) and then the plants were subjected to high-intensity light for 12 hrs (treatment). The results showed that the photosynthetic capacity of young leaf blades was significantly lower than that of mature blades, and, the ability to capture and use light was low for young leaves. In control plants, the parameters of chlorophyll-dependent photochemical efficiency (ФPSII), electron transfer rate (ETR), photochemical quenching coefficiency (qP) and non-photochemical quenching coefficiency (qN) were all significantly lower in younger than mature leaves. There was no significant difference in the photochemical efficiency (Fv/Fm) or light energy distribution parameters between young and mature leaves of control plants. After light treatment, the photosynthetic carbon assimilation capacity and photochemical activity of the PS II reaction center decreased significantly, and both net photosynthetic ratio and chlorophyll b fluorescence parameters changed significantly more than in young leaves than in mature leaves under different PFD. This was particularly evident for Fv/Fm of the young leaves, whose decrease proved that the adaptability of young leaves to convert light was significantly lower than that of mature leaves. Obvious differences in the degree and mechanism of protection against light damage exist between young and mature leaves. Mature leaves dissipated excess excitation energy. In contrast, young leaves dissipated excess excitation by inactivation of the photosynthetic reaction center.